2014
DOI: 10.1136/heartjnl-2013-305314
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of early mortality after transcatheter aortic valve implantation: individual risk assessment using a simple score

Abstract: Early mortality after TAVI is mainly related to age, the severity of symptoms, comorbidities and transapical approach. A simple score can be used to predict early mortality after TAVI. The moderate discrimination is however a limitation for the accurate identification of high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
129
2
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(136 citation statements)
references
References 30 publications
(23 reference statements)
4
129
2
1
Order By: Relevance
“…Studies of EuroSCORE II show an area under the receiver-operating characteristic curve of only 0.7 20 and 0.59 from the French registry. 21 In our study, Logistic EuroSCORE was a predictor of 30-day outcome only when it was extremely high (≥40). This relationship with procedural outcome is reflected in the survival curves, which for Logistic EuroSCORE >40 separate sharply during early follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…Studies of EuroSCORE II show an area under the receiver-operating characteristic curve of only 0.7 20 and 0.59 from the French registry. 21 In our study, Logistic EuroSCORE was a predictor of 30-day outcome only when it was extremely high (≥40). This relationship with procedural outcome is reflected in the survival curves, which for Logistic EuroSCORE >40 separate sharply during early follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…Also in accordance with these results, Barbash et al 19 showed the presence of apical wall motion abnormalities in about one third of the patients treated through the TA approach, which translated into a lower LVEF at follow-up. While the poorer outcomes associated with the TA approach have been mainly related to the higher risk profile of the patients treated through this approach (usually patients with inadequate iliofemoral access) 20 , the TA approach was found to be an independent predictor of mortality in two large TAVI studies (FRANCE-2 and the UK TAVI Registry) 21,22 as well as in a recent meta-analysis 23 . The present study showing that this approach is systematically associated with significant irreversible myocardial injury suggests that the loss of ~5% of the myocardium associated with this approach (>1 g of necrotic mass in all cases) may contribute to these poorer clinical outcomes.…”
Section: Figure 4 Degree and Extent Of Myocardial Necrosis At The Apmentioning
confidence: 99%
“…6,7 Recent studies have developed parsimonious prediction models to facilitate patient selection and counseling for TAVR. [8][9][10] However, a TAVR risk model customized for institutional performance assessment was not previously available.…”
Section: Editorial See P 498mentioning
confidence: 99%